CONSUMERS ATTITUDES TOWARDS MARINATED AND PASTEURISED VEGETABLE - Vesna Rodić; Branislav Vlahović; Zoran Popović (Ekonomika Poljoprivrede (1979), 2007)
Taking into account the importance that marinated and pasteurized vegetables have in human nutrition, particulary in the seasons when needs for vitamins can not be provided from fresh vegetable, authors in the paper analyze consumers attitudes and motives, which are obtained on the bases of conducted survey.